The Effect of Surface Bump Towards EPDM Rubber Brake Hose Performance - A.N. Rosli; A.A. Rashid; A.H. Abdullah (Journal of the Society of Automotive Engineers Malaysia, 2023)
The function of the brake hose is to distribute relatively high-pressure brake fluid to the complete fixed line leading to the brake calipers on the wheel. The flexible Ethylene- polypropylene-dine- monomer (EPDM) rubber used to manufacture the hose allows it to move with the car’s suspension system. During the manufacturing process of this hose, the presence of a surface bump on the outer surface results in significant scrap rates. The objective of this research was to investigate the physical condition as well as mechanical properties of the defective samples in comparison with the normal ones. Scanning Electron Microscopy (SEM) results did not reveal any morphology or elemental composition differences between the two groups of samples. Tensile strength and volumetric expansion T-test probability value (p-value) obtained were higher than 0.005 suggesting that both samples have similar mechanical property performance. The outcome of this study can be used as the preliminary data to perform a further rigorous and stressful test of the bump samples to determine if the defect is just cosmetic and has no reliability issue and hence should be accepted in production.